Orthosymplectic Jordan superalgebrasand the Wedderburn principal theorem (2018)
ABSTRACT: An analogue of the Wedderburn Principal Theorem (WPT) is considered for finite-dimensional Jordan superalgebras A with solvable radical N,N2= 0, and such that A/N∼=Jospn|2m(F), where F is a field of characteristic zero. We prove that the WPT is valid under some restrictions over the irreducible Jospn|2m (F)-bimodules contained in N, and show with counter-examples that these restrictions cannot be weakened.